2013
DOI: 10.1177/0954407013492932
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the trade-off between the part-load fuel efficiency and the transient response for a highly boosted downsized gasoline engine with a supercharger driven through a continuously variable transmission

Abstract: Downsizing is an established trend in the development of passenger car engines. However, the benefits of an improved fuel economy are often obtained at the expense of the engine's dynamic response (owing to increasing demands on the boosting system) and, consequently, the vehicle driveability. The use of a continuously variable transmission in the supercharger driveline offers increased control flexibility over the air path, which could allow more suitable calibrations to be developed. This paper gives details… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…For example, in the simulation study by Rose et al, 80 the clutch acceleration torque can be seen in Figure 13. The engine torque dip phenomenon can also be seen in Figure 14, in which it can be observed that the economy mode (labelled SC disengaged) has a significantly lower engine torque during the first part of a transient event in comparison with the sport mode (labelled SC engaged).…”
Section: Clutch Controlmentioning
confidence: 96%
See 4 more Smart Citations
“…For example, in the simulation study by Rose et al, 80 the clutch acceleration torque can be seen in Figure 13. The engine torque dip phenomenon can also be seen in Figure 14, in which it can be observed that the economy mode (labelled SC disengaged) has a significantly lower engine torque during the first part of a transient event in comparison with the sport mode (labelled SC engaged).…”
Section: Clutch Controlmentioning
confidence: 96%
“…Although some passive bypass valves can function similarly to active bypass valves by tuning the action of 80 For reference, the BMEP target, 90% of the BMEP step demand (i.e. full load) and the equivalent BMEP for the baseline experimental results are also shown.…”
Section: Selection Of the Bypass Valve Typementioning
confidence: 99%
See 3 more Smart Citations